PENGARUH FAKTOR PREDISPOSISI, PENDUKUNG, DAN PENDORONG TERHADAP PENCEGAHAN KECACATAN PASIEN PENDERITA PENYAKIT KUSTA DI RS KUSTA HUTASALEM KABUPATEN TOBASA TAHUN 2012 - Happy R Pangaribuan (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
Disability thats effected from the disease of leprosy is a threat to the human resources who needed for development. Prevalency of leprosy in the world in 2009 The prevention of disability for leprosy’s patients is at the stage of secondary prevention.  Prevention at this stage to limit the disability or illness who are already attacking or infecting. This study is a survey with explanatory research approach that is aims to explain the factors that influence the prevention of leprosy disability. The population in this study were all patients who take treatment at the Hutasalem’s leprosy hospital. Study sample totaled 78 patients. Analysis of data using multiple logistic regression test at the 95% confidence interval. The results indicated that there was a variable effect of knowledge (p < 0.001) and family support (p = 0.002) on the prevention of leprosy disability, whereas the variables  no effect are the level of education, employment, availability of health facilities, and hospital policy. Recommended to the Leprosy Hospital to further enhance the formal education to leprosy’s patients on healthy lifestyle behaviors. In addition, the need for better family support in motivating, assisting even helping patients to treat wounds. Key words: leprosy, knowledge, family support, prevention of disability.